2017
DOI: 10.1016/j.jid.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Phenformin Enhances the Efficacy of ERK Inhibition in NF1-Mutant Melanoma

Abstract: Inactivation of the tumor suppressor neurofibromin 1 (NF1) presents a newly characterized melanoma subtype, for which currently no targeted therapies are clinically available. Pre-clinical studies suggest that ERK inhibitors are likely to provide benefit, albeit with limited efficacy as single agent; therefore, there is a need for rationally designed combination therapies. Here, we evaluate the combination of the ERK inhibitor SCH772984 and the biguanide phenformin. Combination of both compounds showed potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…A recent report showed that phenformin, but not metformin, strongly reduces melanoma cell viability, growth, and abrogates melanoma cell invasion (45). Furthermore, phenformin has been reported to enhance the therapeutic efficacy ofBRAF (V600E) and ERK inhibitors in melanoma (46, 47). The encouraging antitumor efficacy of phenformin in our study, in the context of the disappointing efficacy of metformin in a recent pancreatic cancer clinical trial, suggests that phenformin merits clinical investigation as an anticancer agent for the treatment of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that phenformin, but not metformin, strongly reduces melanoma cell viability, growth, and abrogates melanoma cell invasion (45). Furthermore, phenformin has been reported to enhance the therapeutic efficacy ofBRAF (V600E) and ERK inhibitors in melanoma (46, 47). The encouraging antitumor efficacy of phenformin in our study, in the context of the disappointing efficacy of metformin in a recent pancreatic cancer clinical trial, suggests that phenformin merits clinical investigation as an anticancer agent for the treatment of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of melanoma tumors with MAPK inhibitors increases the H3K4 demethylase JARID1B-positive subpopulation of melanoma cells [ 15 ]. These cells are slow-cycling and treatment-resistant.…”
Section: Main Bodymentioning
confidence: 99%
“…For instance, metformin has been shown to increase the effects of anti-HER2 monoclonal antibody trastuzumab (Herceptin) by suppressing self-renewal and proliferation of cancer stem/progenitor cells in HER2-positive carcinomas (Vazquez-Martin et al, 2011). Similarly, phenformin potentiates the effects of BRAF and ERK inhibitors in BRAF(V600E) and NF1-mutant melanoma cells, respectively, through the selective targeting of JARID1B-expressing subpopulation of cells (Trousil et al, 2017;Yuan et al, 2013). Although that these findings are presently being studied in clinical trials in which biguanides are combined with KIs, the underlying mechanisms and generality of the effects of such combinations are incompletely described.…”
Section: Discussionmentioning
confidence: 99%
“…Combining KIs and phenformin has been shown to be effective in melanoma cells (Trousil et al, 2017;Yuan et al, 2013). We therefore first sought to establish the universality of these findings by combining clinically used KIs and phenformin in cancer cell lines of different origin that harbor diverse activated forms of oncogenic kinases.…”
Section: Phenformin and Lapatinib Exhibit Synergistic Anti-proliferatmentioning
confidence: 99%
See 1 more Smart Citation